Refining the Definition of Student Peer Feedback: The Role of Roles - Carmen Heine; Anja Vesterager (Hermes)
Refining the definition of student peer feedback in text production pedagogy and extending the definition to include the concept of peer-feedback roles, this article roots in higher education and explores definitions of peer feedback based on multiple characteristics. Its primary objective is to contribute to the landscape of student peer-feedback research in writing and translation studies. Its secondary objective is to provide a discourse-sensitive definition of student peer feedback at the crossroads of symbolic interactionism and social constructivism. This article reconceptualizes the role that peer-feedback roles play in student peer-feedback settings, drawing on peer-feedback research to cut across the disciplines. It broadens the perspective on the perceived dichotomy of the roles of feedback provider and receiver, based on role theory as a critical framework to synthesize theoretical approaches. This article suggests future conceptualization and theorization of roles as a framework for educators and researchers.